2005
DOI: 10.1519/1533-4287(2005)19[318:motith]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Talent in Team Handball: The Questionable Use of Motor and Physical Tests

Abstract: Testing for selection is one of the most important fundamentals in any multistep sport program. In most ball games, coaches assess motor, physical, and technical skills on a regular basis in early stages of talent identification and development. However, selection processes are complex, are often unstructured, and lack clear-cut theory-based knowledge. For example, little is known about the relevance of the testing process to the final selection of the young prospects. The purpose of this study was to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
111
1
19

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(144 citation statements)
references
References 0 publications
13
111
1
19
Order By: Relevance
“…These results agree partially with the results observed (i) in elite female team-handball players 9 ; and (ii) in young team-handball players. 3 In fact, it seems that in youth teamhandball players, the skill test could be a good indicator to provide coaches with relevant information in the selection process. Nevertheless, we observed that (in adult male team-handball athletes) the determinants of success are multidisciplinary.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results agree partially with the results observed (i) in elite female team-handball players 9 ; and (ii) in young team-handball players. 3 In fact, it seems that in youth teamhandball players, the skill test could be a good indicator to provide coaches with relevant information in the selection process. Nevertheless, we observed that (in adult male team-handball athletes) the determinants of success are multidisciplinary.…”
Section: Discussionmentioning
confidence: 99%
“…Items are measured on a 3-point scale, from ''Hardly Ever'' 1 to ''Often''. 3 Scores range from 10 to 30, and higher scores indicate higher competitive trait anxiety. Sample items include, e.g.…”
Section: Psychological Profilingmentioning
confidence: 99%
See 2 more Smart Citations
“…The bosco repeated vertical jump test is often applied during an athlete's annual training cycle [3][4][5], when performance is dependent on anaerobic capability. The test is also recommended as a diagnostic search tool for talented individuals involved in anaerobic activities [4,6,7].…”
Section: Introductionmentioning
confidence: 99%